Analisis Integrasi Pasar Karet: Pada Delapan Provinsi Produsen Karet Terbesar di Indonesia - Siti Ramadani Andelia; Mirza Antoni; Dessy Adriani (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Rubber is the country's second largest foreign exchange earner in domestic agricultural products and provides the livelihood for 2.5 million families in Indonesia. Rubber plantations are spread in various provinces of Indonesia which are the second largest rubber producer with the largest plantation area in the world. The purpose of this study is to analyze the integration of the natural rubber market at the producer level and to find out how far changes in prices that occur in one market will cause changes in other markets. The analyzed provinces were eight provinces of Indonesia using the Vector Autoregressive (VAR) and Vector Error Correction Model (VECM) analysis methods using Rstudio and Eviews analysis tools. The price data used is from January 2016 to December 2021. The data obtained are from the SIM of the ministry of agriculture and the plantation service in the eight sample provinces with . The results of this study are that there is a balance and short-term and long-term integration between the largest rubber-producing provinces in Indonesia. Price changes in South Sumatra two months earlier had a negative effect on price changes in North Sumatra Province. Three months earlier, price changes in South Sumatra had a negative relationship with Lampung. This means that the increase in prices in South Sumatra Province in the previous three months led to a decrease in natural rubber prices in Lampung Province this month or vice versa and so on. Lag defined up to lag 3 (three months before) integration analysis supported by Granger causality test supported by IRF and FEVD.